Integrasi Kearifan Lokal dalam Pembelajaran IPS untuk Menumbuhkan Nilai Karakter pada Siswa Sekolah Dasar - Yona Wahyuningsih; Riana Marthalivia Jauhar; Shiva Aqila Zikri (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
Social Studies (IPS) learning in elementary schools plays a strategic role in developing social thinking skills and shaping students’ character rooted in national culture. However, learning practices still tend to focus on cognitive aspects, so character building is not yet optimal. This study aims to analyze the integration of local wisdom in social studies learning as an effort to strengthen the character of elementary school students. The method used is a Systematic Literature Review (SLR) through a review of various national and international journals, reference books, and related education policies. The results show that the integration of local wisdom serves as a source of contextual learning and an effective means of internalizing the values of mutual cooperation, responsibility, honesty, teamwork, and love for the country. The success of its implementation depends on the creativity of teachers and community involvement. Thus, the integration of local wisdom in social studies learning has the potential to strengthen student character and preserve national culture.